Syntax, Power, and Persuasion: Linguistic Strategies in Political and Media Discourse - Ishak Bagea; Mentari Putri Pramanenda Sinaga; Sitti Agustina (Journal of Humanities Research Sustainability, 2026)
Background. Language plays a pivotal role in shaping political power and influencing public opinion. Through syntax, rhetorical strategies, and discourse structures, political and media discourses manipulate language to persuade, construct ideologies, and reinforce power dynamics. Understanding the linguistic strategies used in these contexts is essential for analyzing how political narratives are constructed and how media discourse frames societal issues. Purpose. This study aims to explore the syntactic and linguistic strategies employed in political and media discourse, focusing on how these strategies serve to exert power, persuade audiences, and reinforce ideological structures. The research seeks to identify common patterns of persuasion and power dynamics within language use and to evaluate their impact on public perception. Method. A qualitative approach is used, with a combination of discourse analysis and syntactic analysis to examine political speeches, media articles, and televised debates. Data is collected from a range of political figures, media outlets, and speeches within the last decade to assess the contemporary use of language as a tool for persuasion and ideological influence. Results. The findings indicate that political and media discourses employ complex syntactic structures, including parallelism, modality, and presupposition, to assert authority and influence audience beliefs. These strategies are closely tied to ideological positioning, with frequent use of inclusive language to consolidate power and exclusive language to marginalize opposition. Conclusion. This research highlights the role of syntax in shaping political and media narratives. Understanding these linguistic strategies allows for a deeper analysis of how power and persuasion function within public discourse, contributing to the manipulation of public opinion and the reinforcement of social and political hierarchies.